Dynamics of human facial aging through photoanthropometric analysis and quadratic modeling from child- to adulthood – a multi-centric study: A multi-centric study (Revista Brasileira de Ciências do Envelhecimento Humano, 2020)
This study aimed to investigate the dynamics of facial aging from photographs of individuals in different age groups and establish a pattern of facial growth. The sample consisted of digital photographs standardly taken from 1273 Brazilians aged between 2 and 24 years and equally distributed by sex into 12 specific age groups (2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22 and 24 years). SAFF-2D® (Forensic Facial Analysis System, Brazilian Federal Police, Brazil) software package was used for positioning 28 landmarks on each photograph. Two-hundred and eight measurements were established between the landmarks. Photoanthropometric Indicators (PAI) of facial morphological alterations were obtained from the relations of facial measurements with a fixed reference (diameter of the iris). Non-transformed linear, quadratic and log-linear models were tested to screen the best approach to describe the facial growth with aging in females and males. The quadratic model reached the best outcomes in females (R2